PENEGAKAN KODE ETIK PROFESI POLRI DI BIDANG PROFESI DAN PENGAMANAN (BIDPROPAM) POLDA JATENG - Kelik Budiono (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2014)
The Government of Indonesia has issued legislation governing dismissal Police officers who committed the crime, stated in Government Regulation No. 1 of 2003 Article 11, paragraph 1, letter a, and the Police Regulation No. 14 of 2011 on the Police Ethic Code, however, there are still police officer(s) who violate the Police Ethic Code. The enforcement implementation of the Police Ethic Code in the Bidpropam of Central Java Police based on the Police Regulation No. 14 of 2011 Article 21 was carried out by the Police Ethic Code Commission in accordance with Police Regulation 19 of 2012 Article 30 against the perpetrators of criminal acts and who have obtained legally binding court decision, through Court of Police Ethic Code Commission against criminals for getting Dismissal Decision With No Honor. Constraints in the enforcement of Police Ethic Code in Bidpropam of Central Java Police is the disharmony between Article 17 and Article 22 of the Police Regulation, No. 14 of 2011, the limited power accreditor and limited working room, the Police Ethic Code Commission could be fickle, the courtroom is not permanent, human resource, namely accreditor,should be really professional.